A photojournalist on assignment - Souza, Pete (Kansas State University, 2006)
This report is based on an exhibition of 37 photographs at the Kemper Gallery in the Student Union of Kansas State University. All photographs presented here and in the exhibit were created during the past 28 years of my career. Hence the exhibit is a mid-career retrospective. My photojournalism experience is very unique in that I am the only photojournalist in the world who has worked as a presidential photographer, published photo essays in National Geographic Magazine as a freelancer, and been on the staff of a large metro newspaper. The photographs chosen for the exhibit were highlighted by, but not limited to, assignments from those three experiences. This report mirrors the exhibit except for a few additional photographs that, because of space limitations, didn’t make it into the final edit for the exhibit. There are three sections: Moments from Kansas to Papua New Guinea, The Presidency, and After 9/11. The “moments” section presents a wide variety of photographs from a wide variety of assignments. The “presidency” section focuses on my tenure as Official White House Photographer for President Reagan, and also includes photographs of the Reagan funeral, other presidents, and a possible future president. “After 9/11” begins at the Pentagon on 9/12, and then follows the course of events in Afghanistan during the following weeks. Extensive captions accompany most of the photographs. The captions are written in the third person which is customary for gallery exhibitions. More than the who, what, where and when, they provide some additional context and are intended to inform both the journalism student and the layperson.
Keywords: Photojournalism; Journalism; Photography; Afghanistan; President Reagan; Presidency; Fine Arts (0357); Journalism (0391); Mass Communications (0708)